Analysis of mouse models of insulin secretion disorders - Kaizik, S (2010)
In this thesis, three mouse models and cell culture techniques were used to investigate genetic factors leading to glucose intolerance, diabetes or hyperinsulinemia. Loss of nicotinamide nucleotide transhydrogenase (Nnt) function is linked to ROS-mediated uncoupling of mitochondrial metabolism and reduced insulin secretion. The enzymatic activity of Nnt generates mitochondrial NADPH essential for ROS detoxification. However, the exact nature of ROS as well as the antioxidant enzymes involved are still unknown. It was found that MIN6 cells in which Nnt was silenced displayed an increase in mitochondrial H2O2 upon stimulation with both the ROS generator menadione and glucose. Knockdown of GPx1, however, had no effect on mitochondrial H2O2 and was linked to a Ca2+ independent hypersecretion of insulin. Exogenous GSH did not increase the glucose-stimulated rise in [Ca2+]i in Nnt mutant and control islets. This finding substantiates the suggested role of ROS as a signalling molecule in insulin secretion. In contrary to previous studies on MIN6 cells and single β-cells, the glucose-stimulated increase in [Ca2+]i, measured in intact Nnt mutant islets showed no difference compared with control islets. This might indicate differences in single β-cell versus whole islet physiology or be attributable to differences in genetic background. The activating V59M mutation in the KATP channel subunit Kir6.2 causes neonatal diabetes in humans. Transgenic mice constitutively expressing the V59M mutation in their β-cells recapitulated features of the disease phenotype in humans. In vitro studies showed that β-cells exhibited impaired first- and second-phase glucose-dependent insulin secretion. This was paralleled by a complete loss of the initial glucose-dependent rise in [Ca2+]i in V59M islets. However, islets from mice carrying an uninduced Kir6.2-V59M mutation, or mice expressing Cre recombinase, showed no impairment of their [Ca2+]i responses. If expression of the transgene was induced but mice were then treated with the KATP channel blocker glibenclamide to control their diabetes, isolated islets displayed a loss of the initial rise in [Ca2+]i and a reduced sustained increase of [Ca2+]i, which was associated with abrogation of synchronous Ca2+ oscillations in β-cells. In the presence of glibenclamide, both basal Ca2+ levels and insulin secretion from isolated islets were elevated, whereas the glucose-stimulated [Ca2+]i response, synchronicity of Ca2+ oscillations and insulin secretion were restored. Furthermore, Ca2+ imaging revealed that the number of β-cells per islet responding to glucose was similar to control islets, underlining the importance of early treatment with glibenclamide to achieve glycemic control. The E1506K mutation of the SUR1 subunit of the KATP channel causes a reduction in channel activity. It is associated with hyperinsulinism of infancy in early life and leads to the development of glucose intolerance, insulin deficiency and diabetes later in life. Islets isolated from a knock-in mouse expressing the SUR1-E1506K mutation showed enhanced glucose-stimulated insulin secretion from young het E1506K (first- and second-phase) and young hom E1506K islets (basal and first-and second-phase). Old hom E1506K islets exhibited normal basal insulin secretion but first- and second-phase secretion was found to be markedly reduced in comparison to wild-type islets. This was due to a decline in insulin content. Confocal Ca2+ imaging suggested that this was not caused by β-cell loss. Measurements of [Ca2+]i in young het E1506K islets showed spontaneous Ca2+ oscillations in 2 mM glucose, which did not result in an average elevation in [Ca2+]i. However, young hom-E1506K islets displayed vigorous Ca2+ oscillations in 2 mM glucose that led to an average elevation in [Ca2+]i. Depolarisation of E1506K islets with either glucose, tolbutamide or KCl produced a reduced increase in [Ca2+]i compared to wild-type islets indicating either a reduction in Ca2+ influx or an enhanced clearance of Ca2+. Peak voltage-dependent inward currents recorded from β-cells in het-E1506K islets were larger than in wild-type β-cells. Untypically for mouse β-cells, these inward currents contained a Na+ current resulting from a shift in its inactivation towards a more positive membrane potential.